Correction: Nanochannel conduction in piezoelectric polymeric membrane using swift heavy ions and nanoclay. Issue 11 (25th February 2022) - Jana, Karun Kumar; Vishwakarma, Niraj Kumar; Ray, Biswajit; Khan, Saif A.; Avasthi, Devesh K.; Misra, Manjusri; Maiti, Pralay
Abstract : Correction for 'Nanochannel conduction in piezoelectric polymeric membrane using swift heavy ions and nanoclay' by Karun Kumar Jana et al., RSC Adv., 2013, 3, 6147–6159. DOI: ; 10.1039/C3RA23176C